Assessment and Containment of Aflatoxin Impact on the Health by Solar Drying - Gupta, Smriti; Verma, Shishir Kumar; Kumar, Sanjay (Journal of the Institute of Engineering, 2020)
Solar drying is well known to human being since time immemorial. Its impact on our life is multidimensional. However, gradual changes in our life style have consistently reduced its positive impact during last century. It is more evident in towns. One of them is contamination of dietary items by fungi, which produces carcinogens. The ubiquitous fungus Aspergillus flavus is notorious for contaminating many important crops and food stuffs with the carcinogenic mytoxin, aflatoxin. The Aspergillus spp., are widely spread in nature and contaminated food supplies of humans and animals resulting in health hazards and even death. A detail survey of wholesale depots was made to assess the impact of aflatoxin on the health of the human and other animals by the natural contamination of the dietary items. Samples of different dietary items collected from different wholesale depots belonging to five different mohallas of Darbhanga town (Bihar, India) during 2012 were brought to the laboratory for further studies. The findings suggest that Aspergillus flavus appeared as the most dominant mycoflora in general. Present bioassay on Daphnia magna subjected to static exposure of different concentration of A. flavus crude extract clearly indicate the stain to be potential toxic producer. The rate of mortality increased with increased in amount of toxin. Solar drying is a cost-effective solution to overcome this serious problem. The technology is well developed and tested. In this paper, appropriate solar dryer design is further proposed for households to eliminate this serious health hazard.